ChemInform Abstract: 25th Anniversary Article: MXenes: A New Family of Two‐Dimensional Materials. Issue 17 (28th April 2014) - Naguib, Michael; Mochalin, Vadym N.; Barsoum, Michel W.; Gogotsi, Yury
Abstract Review: MXenes: early transition metal carbides or carbonitrides resulting from the selective removal of the A element from ternary carbides called MAX phases like Ti2AlC, Ti3AlC2, or Ta4AlC3; 70 refs.